Implementation of Prototype Method for Developing Website-Based Eyeglass Sales Information System - Winanti, Winanti; Wibowo, Galih Surya; Maulana, Muhammad; Setiawan, Rizky; Fenolia, Sheila; Kusumawati, Wisnu Dewi; Marwah, Siti; Anshori, Rizki Irfan; Sanjaya, Andi; Basuki, Sucipto; Nursiastuti, Nurasiah; Luthfian, Muhamad (International Journal of Innovation Research in Education, Technology and Management, 2025)
Sales of glasses including lenses, cleaning fluids, frames and other supporting products are still carried out conventionally and prospective buyers must come directly to the store. Sales reporting is also still done by recording the results of sales notes in the ledger resulting in frequent recording errors. Current reports cannot be done in real time so they are less efficient and effective. Sales are done by word of mouth and by using WhatsApp status updates with limited reach. An online or digital eyeglass sales system is needed at Optic XYZ so that the reach is wider, buyers do not have to come and reports are fast, precise and accurate and real time. System development using prototype and website-based methods. In order to ensure that the system can be implemented properly and without obstacles, a trial was carried out using the black box testing method involving users in testing. The system was built to overcome sales and reporting problems so that with this sales system it can help buyers and admins and optic parties in sales and reporting. After the system is implemented, in the future a mobile-based eyeglass sales system will be developed at Optic XYZ so that the system continues to develop and follows the latest technological advances.